Preliminary Study on The Implementation of STEM-Integrated Problem-Based Learning in Elementary School Education - Lestari, Rini Dwi; Triyanto, Triyanto; Sudiyanto, Sudiyanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Twenty-first century learning requires instructional approaches that develop higher-order thinking skills and connect learning materials to students’ real-life experiences. This study aimed to describe the implementation of STEM-integrated problem-based learning at SD Negeri 3 Kujon in IPAS learning. The study employed a qualitative descriptive approach, with data collected through classroom observations, teacher interviews, and analysis of instructional documents. The findings revealed that lesson planning was aligned with the Learning Outcomes and Learning Objectives of the Merdeka Curriculum and incorporated contextual problems relevant to students’ experiences. The implementation of learning successfully increased students’ active engagement through discussions, group collaboration, and problem-solving activities, while teachers acted as facilitators. Students also demonstrated positive responses characterized by high enthusiasm, interest, and participation during the learning process. The study concludes that STEM-integrated problem-based learning effectively supports active, contextual, and meaningful IPAS learning in accordance with the principles of the Merdeka Curriculum in elementary schools.